Sociodemographic and psychological differences between levels of vaccination intention among pregnant mothers - Mohd Nazori, Mohd Nazir; Ismail, Rohani; Rasudin, Nur Syahmina (Universiti Putra Malaysia, 2025)
Introduction: Vaccination intention is a prospective variable to screen for potential vaccine refusal. Improving the level of vaccination intention requires tailoring the approach of intervention according to the sociodemographic and psychological characteristics of the parents. Health literacy, health self-efficacy, and health assertiveness were proposed as relevant psychological characteristics for consideration in health educational intervention. This study aimed to identify significant differences in health self-efficacy, health assertiveness, and health literacy between vaccination intention levels among pregnant mothers. Materials and methods: A cross-sectional survey was done multi-stage random sampling involving pregnant mothers from maternity and child health clinic in district of Petaling, Klang, Gombak, and Hulu Langat. A random subset of 172 respondents were chosen from the larger study sample to address the objective to be consistent with sample size calculated. Data was analysed using SPSS version 27 for descriptive statistics and chi-squared, independent t-tests, and two-way ANOVA for inferential statistics. Results: Education level (p = 0.022), household income level (p = 0.004), health assertiveness (p < 0.001), and health literacy (p = 0.003) showed significantly higher value in high vaccination intention groups. Health self-efficacy showed no significant differences between the two groups. Multivariate analysis reported no interaction effects between the groups. Conclusion: Each of the characteristics warrant a tailored approach to intervention for improving or maintaining the levels of vaccination intention. Both significant characteristics were conceptually related to vaccination knowledge, hence supporting the importance of tailored health education to pregnant mothers.